2011
DOI: 10.1061/(asce)cc.1943-5614.0000218
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strengthening of RC Beams with Cement-Based Composites

Abstract: In this paper, the effectiveness of fiber-reinforced cementitious matrix (FRCM) materials for the strengthening of reinforced concrete (RC) beams is experimentally investigated. Bending tests on RC beams strengthened with different FRCM materials, made out of (1) carbon fiber nets; and (2) poliparafenilenbenzobisoxazole (PBO) fiber nets embedded in cement-based matrix, are performed. For case (2), different net shapes, cementitious matrices, and a number of net layers were considered. Depending on the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
0
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(126 citation statements)
references
References 17 publications
6
104
0
16
Order By: Relevance
“…Furthermore, some research works were performed to evaluate the effectiveness of FRCM for the flexural strengthening of RC beams. D'Ambrisi and Focacci [4] investigated the effect of fiber net material (PBO and carbon FRCM), the type of mortar matrixes and the strengthening scheme (different U-wrapping configurations) on the flexural behavior of FRCM-strengthened beams having an internal reinforcement ratio of 0.11…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, some research works were performed to evaluate the effectiveness of FRCM for the flexural strengthening of RC beams. D'Ambrisi and Focacci [4] investigated the effect of fiber net material (PBO and carbon FRCM), the type of mortar matrixes and the strengthening scheme (different U-wrapping configurations) on the flexural behavior of FRCM-strengthened beams having an internal reinforcement ratio of 0.11…”
Section: Previous Researchmentioning
confidence: 99%
“… It was found that RC concrete beams reinforced with two layers of PBO FRCM, which yields an axial stiffness of approximately 83% of one layer of carbon FRP sheets, provided about a 30% increase in the ultimate load, which was almost the same increase as the CFRP strengthening. Meanwhile, two layers of carbon FRCM with an axial stiffness of about 75% that of CFRP, enhanced the ultimate load by only 15% [4].…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the bonding behaviour at the FRP-to-concrete interface may deteriorate due to environmental factors, such as moisture, high temperature and fire [8,9] because of the organic property of the epoxy material. Therefore, some scholars have attempted to utilize inorganic cementitious materials to replace the epoxy resin to develop new fibre composite systems, such as dry fibre sheets bonded with cementitious materials [10][11][12][13][14][15], fibre-reinforced inorganic polymer (FRIP) composites [16,17] and textile reinforced mortars (TRM) [18][19][20][21] for strengthening RC members. The advantages of the inorganic bonding materials are their high resistance to ultraviolet (UV), reduced environmental impact, better resistance to elevated temperature and moisture, as well as better compatibility with the substrate concrete.…”
Section: Introductionmentioning
confidence: 99%